2022
DOI: 10.1088/1674-1056/ac48fd
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of the 107 Ag neutron capture cross sections with pulse height weighting technique at the CSNS Back-n facility

Abstract: Silver indium cadmium (Ag-In-Cd) control rod is widely used in pressurized water reactor nuclear power plants, and which is continuously consumed in a high neutron flux environment. The mass ratio of 107Ag in Ag-In-Cd control rod is 41.44%. To accurately calculate the consumption value of the control rod, a reliable neutron reaction cross section of the 107Ag is required. Meanwhile, 107Ag is also an important weak r nuclei. Thus, the cross sections for neutron induced interactions with 107Ag are very important… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 50 publications
(71 reference statements)
0
3
0
Order By: Relevance
“…However, when it is irradiated again at nearly 1700 s a little displacement damage appears. As for pixel2 [27,4] and pixel4 [131,3], a little displacement damage appears after an accumulated neutron fluence of about 5×10 9 neutrons•cm −2 even though they are irradiated again at nearly 1700 s. As for pixel1 [26,1], a little displacement damage appears after the accu-mulated neutron fluence reaches about 5×10 9 neutrons•cm −2 . However, when it is irradiated again at nearly 1700 s the pixel is twice damaged by the neutrons and reaches the saturation state.…”
Section: Hot Pixelsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, when it is irradiated again at nearly 1700 s a little displacement damage appears. As for pixel2 [27,4] and pixel4 [131,3], a little displacement damage appears after an accumulated neutron fluence of about 5×10 9 neutrons•cm −2 even though they are irradiated again at nearly 1700 s. As for pixel1 [26,1], a little displacement damage appears after the accu-mulated neutron fluence reaches about 5×10 9 neutrons•cm −2 . However, when it is irradiated again at nearly 1700 s the pixel is twice damaged by the neutrons and reaches the saturation state.…”
Section: Hot Pixelsmentioning
confidence: 99%
“…It can be used for nuclear data measurement, neutron resonance radiography and analysis of radiation damage. [4][5][6][7] Charge-coupled devices (CCDs) are widely used in many space environments, such as star tracking, space remote sensing and space object detection. However, when used in these applications they can be seriously damaged by particles or rays, leading to degradation of image quality or even functional failure.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that brown adipocytes or beige adipose cells are present in WAT [11]. Stimulating fat browning involves expression of phenotypic proteins that contribute to the formation of brown adipocytes, including T-box protein 1 (Tbx-1), trans-membrane protein 26 (Tmem26), PR domain 16 (Prdm16), and cluster of differentiation 40 (Cd40) [12][13][14][15]. Brown and beige-like adipocytes have high mitochondrial content.…”
Section: Introductionmentioning
confidence: 99%